Drop-jump landing varies with baseline neurocognition: Implications for anterior cruciate ligament injury risk and prevention - Herman, D. C.; Barth, J. T. (The American Journal of Sports Medicine, 2016)
Background: Neurocognitive status may be a risk factor for anterior cruciate ligament (ACL) injury. Neurocognitive domains such as visual attention, processing speed/reaction time, and dual-tasking may influence ACL injury risk via alterations to neuromuscular performance during athletic tasks. However, the relationship between neurocognition and performance during athletic tasks is not yet established. Hypothesis: Athletes with low baseline neurocognitive scores will demonstrate poorer jump landing performance compared with athletes with high baseline neurocognitive score. Study Design: Controlled laboratory study. Methods: Neurocognitive performance was measured using the Concussion Resolution Index (CRI). Three-dimensional kinematic and kinetic data of the dominant limb were collected for 37 recreational athletes while performing an unanticipated jump-landing task. Healthy, nonconcussed subjects were screened using a computer-based neurocognitive test into a high performers (HP; n = 20; average CRI percentile, 78th) and a low performers (LP; n = 17; average CRI percentile, 41st) group. The task consisted of a forward jump onto a force plate with an immediate rebound to a second target that was assigned 250 milliseconds before landing on the force plate. Kinematic and kinetic data were obtained during the first jump landing. Results: The LP group demonstrated significantly altered neuromuscular performance during the landing phase while completing the jump-landing task, including significantly increased peak vertical ground-reaction force (mean ± SD of LP vs HP: 1.81 ± 0.53 vs 1.38 ± 0.37 body weight [BW]; P < .01), peak anterior tibial shear force (0.91 ± 0.17 vs 0.72 ± 0.22 BW; P < .01), knee abduction moment (0.47 ± 0.56 vs 0.03 ± 0.64 BW × body height; P = .03), and knee abduction angle (6.1° ± 4.7° vs 1.3° ± 5.6°; P = .03), as well as decreased trunk flexion angle (9.6° ± 9.6° vs 16.4° ± 11.2°; P < .01). Conclusion: Healthy athletes with lower baseline neurocognitive performance generate knee kinematic and kinetic patterns that are linked to ACL injury. Clinical Relevance: Neurocognitive testing using the CRI may be useful for identification of athletes at elevated risk for future ACL injury.